Consumers’ attitudes towards purchase intention for local brand automobiles manufactured in Malaysia - Chinedu, Anyanwu Hilary; Haron, Sharifah Azizah; Hashim, Ahmad Hariza; Ho, Jo Ann (Growing Science, 2021)
The damaging effects of market globalization towards developing countries necessitate the exhibition of favorable attitudes towards purchase intention for local brand automobiles manufactured locally. With the application of moral foundation theory (MFT), a quantitative and cross-sectional study that involved 373 Proton potential consumers through a mall intercept survey in Malaysia was analyzed. The results show that Proton’s potential consumers had favorable attitudes towards purchase intention for Proton automobiles. Subsequent to a high mean score of collectivism and a moderate mean score of ethnocentrism, Proton potential consumers’ ethnocentric tendency offers a contradiction to extant literatures on consumer ethnocentrism in developing countries. Thus, our study posits that consumers from collectivistic societies are ethnocentric and further display favorable attitudes towards local products. Additionally, the predictive effects of consumer ethnocentrism and collectivism on attitudes towards purchase intention for local brand automobiles manufactured locally were ascertained. Our findings validated the applicability of MFT in explaining consumers’ attitudes towards local products. Other implications are also discussed.